Laparoscopic Adrenalectomy: posterior retroperitoneoscopic or lateral transperitoneal approach? (Revista Argentina de Cirugía, 2021)
Objetive: to compare the results of posterior retroperitoneoscopic (PRA) or lateral transperitoneal approach (LTA) in laparoscopic adrenalectomy in the short and medium term.Material y methods: prospective cohort study. We included 22 patients who underwent 24 adrenalectomies (12 PRA and 12 LTA) between January 2015 and May 2016. In the PRA group, two simultaneous bilateral laparoscopic adrenalectomies were performed (1 synchronous bilateral adrenalectomy). Baseline, clinical and surgical outcome were compared.Results: the median follow-up time was 6.5 months (range: 1-16). The PRA and LTA groups were comparable in age, gender, BMI and presence of previous surgeries. Adenomas were the predominant lesions (41.7% in each group). The average operating time in PRA and LTA was 104.3 ± 21.2 and 146 ± 32.9 minutes, respectively (p=0.05). We found no differences in length of hospital stay, bleeding and complications. All patients achieved clinical cure.Conclusions: the PRA technique is a safe approach, with results comparable to LTA and shorter opera- ting time. It also allows to intervene simultaneously and synchronously both adrenal glands without the need of repositioning the patient.
Keywords: laparoscopic adrenalectomy; posterior retroperitoneal approach; adrenal tumors